Government and Community Support Strengthening Micro, Small, and Medium Enterprises' Competitive Advantage through Internal Capability - Mustika Dewi; Bambang Suseno; Mhd Harry Azhari As'ad (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study examines the role of government and community support in enhancing Micro, Small, and Medium-sized Enterprises (MSMEs) competitive advantage through internal capabilities. Although external support has been widely recognized as a key driver of MSME performance, few studies have explained how these various support providers enhance competitive advantage through the development of organizational capabilities.Research Methodology: A quantitative cross-sectional survey of 100 MSMEs affiliated with the North Sumatra Chamber of Commerce and Industry (KADIN) was analysed using PLS-SEM in SmartPLS 3. Internal Capabilities were modeled as a higher-order construct comprising Leadership, Entrepreneurial Motivation, and Financial Competence.Results: Government support has a significant impact on both internal capabilities and competitive advantage, whilst community support significantly strengthens internal capabilities but does not directly influence competitive advantage. Internal capabilities have a significant positive influence on competitive advantage and act as a mediator in the relationship between external support and competitive advantage.Conclusions: External support contributes to the competitiveness of MSMEs through various strategic mechanisms, with internal capacity acting as the primary channel for transforming external support into a sustainable competitive advantage.Limitations: This study employs a cross-sectional design and focuses on MSMEs that are members of KADIN in North Sumatra.Contributions: This study extends the literature by conceptualizing Internal Capabilities as a higher-order construct integrating Leadership, Entrepreneurial Motivation, and Financial Competence to explain MSME competitive advantage.